2019
DOI: 10.1111/1471-0307.12668
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of enzymatic‐hydrolysed proteins of dromedary (Camelus dromedarius) colostrum

Abstract: This work investigated the antioxidant activities of dromedary colostrum proteins before and after hydrolysis by pepsin, trypsin, α‐chymotrypsin, pancreatin and papain. The enzymatic hydrolysis affected the degrees of hydrolysis, electrophoretic profiles, molecular weight distribution and hydrophobic/hydrophilic properties of the generated peptides. The antioxidant activities were evaluated using four antioxidant assays, including 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) and 2,2′‐azinobis(3‐ethylbenzothiazoline‐6‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…What is more, there is a significant positive correlation between hydrolysis time and the DPPH radical scavenging activity of WPH. Our study is in agreement with the study by OLFAOUSSAIEF, where the antioxidant activity of all dromedary colostrum hydrolysates were significantly more effective than single peak colostrum proteins [ 28 ]. Similarly, Zheng et al [ 21 ] demonstrated that the rate of free radical scavenging decreased with increasing hydrolysis, indicating a negative correlation between DH and DPPH free radical scavenging activity in oat protein hydrolysis products.…”
Section: Resultssupporting
confidence: 93%
“…What is more, there is a significant positive correlation between hydrolysis time and the DPPH radical scavenging activity of WPH. Our study is in agreement with the study by OLFAOUSSAIEF, where the antioxidant activity of all dromedary colostrum hydrolysates were significantly more effective than single peak colostrum proteins [ 28 ]. Similarly, Zheng et al [ 21 ] demonstrated that the rate of free radical scavenging decreased with increasing hydrolysis, indicating a negative correlation between DH and DPPH free radical scavenging activity in oat protein hydrolysis products.…”
Section: Resultssupporting
confidence: 93%
“…The IC 50 values for the other hydrolysates were between 0.437 and 0.836 mg/mL. These results are in agreement with the hydrolysates from dromedary colostrum proteins ( 16 ). However, Oh et al .…”
Section: Resultssupporting
confidence: 88%
“…The IC 50 values for the other hydrolysates were between 0.437 and 0.836 mg/ mL. These results are in agreement with the hydrolysates from dromedary colostrum proteins (16). However, Oh et al (40) reported higher IC 50 values for cow's milk protein hydrolysates than those in the present study.…”
Section: Effects Of Enzymatic Hydrolysis On the Antioxidant Activities Of Dromedary Milk Proteinssupporting
confidence: 90%
See 1 more Smart Citation
“…This specific composition of colostrum may reveal particular biological activities. Antioxidant activity is among the fundamental biological activities important for life (Oussaief et al, 2020).…”
Section: Introductionmentioning
confidence: 99%